2013
DOI: 10.7448/ias.16.3.18734
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of interventions to reduce HIV‐related stigma and discrimination from 2002 to 2013: how far have we come?

Abstract: IntroductionHIV-related stigma and discrimination continue to hamper efforts to prevent new infections and engage people in HIV treatment, care and support programmes. The identification of effective interventions to reduce stigma and discrimination that can be integrated into national responses is crucial to the success of the global AIDS response.MethodsWe conducted a systematic review of studies and reports that assessed the effectiveness of interventions to reduce HIV stigma and discrimination between 1 Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
635
6
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 569 publications
(659 citation statements)
references
References 102 publications
(92 reference statements)
8
635
6
10
Order By: Relevance
“…Two recent systematic reviews explored the effect of interventions to reduce HIV stigma in HCP (Sengupta, Banks, Jonas, Miles, & Smith, 2011;Stangl, Lloyd, Brady, Holland, & Baral, 2013). Sengupta and colleagues (2011) noted that, of the 19 studies that met their inclusion criteria, 14 demonstrated effectiveness in reducing HIV stigma.…”
Section: Interventions To Increase Knowledge Enhance Willingness To mentioning
confidence: 99%
“…Two recent systematic reviews explored the effect of interventions to reduce HIV stigma in HCP (Sengupta, Banks, Jonas, Miles, & Smith, 2011;Stangl, Lloyd, Brady, Holland, & Baral, 2013). Sengupta and colleagues (2011) noted that, of the 19 studies that met their inclusion criteria, 14 demonstrated effectiveness in reducing HIV stigma.…”
Section: Interventions To Increase Knowledge Enhance Willingness To mentioning
confidence: 99%
“…Despite extensive efforts in HIV education, HIV-related stigma still exists in health care (Shah, Heylen, Srinivasan, Perumpil, & Ekstrand, 2014). Since the first global review of interventions to reduce HIV-related stigma (Brown, Macintyre, & Trujillo, 2003), two additional systematic reviews have been conducted to evaluate the impact of interventions to increase HIV knowledge, decrease stigma, improve infection control practices, and increase willingness by HCP to treat PLWH (Sengupta, Banks, Jonas, Miles, & Smith, 2011;Stangl, Lloyd, Brady, Holland, & Baral, 2013). Sengupta and colleagues (2011) reviewed 19 studies, including four interventions to evaluate nurses' willingness to provide care for PLWH.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Internalised stigma affects individuals' self-esteem (Nam et al, 2008;Tsai et al, 2013), while experienced stigma relates to discrimination by others (Liu et al, 2011;Peitzmeier, Grosso, Bowes, Ceesay, & Baral, 2015). Growing availability of ART appears to have reduced HIV stigma (Campbell et al, 2011;Roura et al, 2009) alongside interventions to change public attitudes (Stangl, Lloyd, Brady, Holland, & Baral, 2013;Tsai et al, 2016).…”
Section: Introduction (1520 Words)mentioning
confidence: 99%